2015
DOI: 10.1155/2015/835074
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Primary Language, and Income Are Not Demographic Drivers of Mortality in Breast Cancer Patients at a Diverse Safety Net Academic Medical Center

Abstract: Objective. To examine the impact of patient demographics on mortality in breast cancer patients receiving care at a safety net academic medical center. Patients and Methods. 1128 patients were diagnosed with breast cancer at our institution between August 2004 and October 2011. Patient demographics were determined as follows: race/ethnicity, primary language, insurance type, age at diagnosis, marital status, income (determined by zip code), and AJCC tumor stage. Multivariate logistic regression analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…A more recent study conducted in a safety net hospital reported an over 2-fold increase in breast cancer mortality in single versus married breast cancer patients [5]. However, none of these studies examined whether the marital status effects on survival differ across patient subgroups or tumor subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study conducted in a safety net hospital reported an over 2-fold increase in breast cancer mortality in single versus married breast cancer patients [5]. However, none of these studies examined whether the marital status effects on survival differ across patient subgroups or tumor subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence shows that mortality following a cancer diagnosis is higher in unmarried than married patients [ 1 4 ]. However, studies on the association specific to breast cancer are limited [ 5 , 6 ], despite this being the most common cancer in women. Some published reports included marital status as a covariate in multivariable analyses [ 7 9 ], but, to our knowledge, a focused examination of the specific effect of marital status on breast cancer survival in different racial/ethnic populations or by tumor subtype has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulus control limits the activities performed in bed to sleep and sex only so as to recondition the bed to be associated with sleep as opposed to wakefulness. Sleep restriction and stimulus control can produce a temporary worsening of daytime sleepiness and discomfort and are thought to be the most difficult components for patients to adhere to (Parikh et al, 2015). Sleep hygiene serves to promote behaviors and practices that facilitate sleep and to discourage behaviors and practices that are thought to contribute to insomnia.…”
Section: Methodsmentioning
confidence: 99%
“…World widely; around 6.6% of all breast cancer cases were diagnosed in women less than 40 of age [3] and in USA 6.7% of patients were <40 y and 29.8% were <50 y [15]. In this study, 66 & 98 patients out of 292 (22.6% & 33.56%) were <40 & ≤40 years old respectively, and 199 patients out of 292 (68.2%) were <50 years old, where they are obviously higher than above stated word wide and USA indices, but they are compatible with Arabic study that included 8 Arabic countries 65.5% (±11) [5].…”
Section: Age Of Presentationmentioning
confidence: 99%